Traditional Retail Business Marketing Strategy in Dealing Business Competition - Wulandari, Deasy; MSi, SE (International Journal of Engineering and Technology, 2019)
This study was conducted based on the traditional retail business phenomenon in Jember in dealing the competition of modern retail business. The rapid growth of modern retail business led to increasing levels of competition faced by traditional retailers. Traditional retailers must have a marketing strategy in order to survive in retail business competition. The purpose of this study are: (1) to identify the strengths, weaknesses, opportunities and threats on traditional retail; (2) to formulate the appropriate marketing strategy for traditional retailers in dealing modern retail competition. The research method used is descriptive qualitative method. The analysis technique used in this study is TOWS analysis. The informants are: business owners, employees, consumers and stakeholders. The results showed: (1) the strengths of traditional retailers are : strategic location, communications, word of mouth, uniqueness; traditional retail weaknesses are: the layout of items, homogeneity of products, quality of service; traditional retail opportunities are : culture, government regulations, needs and desires of the community; traditional retail threats are : a shift in culture, growth and development of modern retail; (2) the formulation of a marketing strategy that should be implemented to deal with the modern retail competition are : diversity andÂ  innovation of the products offered, improving the quality of services, an increase in information and technology.Â